2019
DOI: 10.3389/fnins.2018.01039
|View full text |Cite
|
Sign up to set email alerts
|

Pupillometry of Groove: Evidence for Noradrenergic Arousal in the Link Between Music and Movement

Abstract: The capacity to entrain motor action to rhythmic auditory stimulation is highly developed in humans and extremely limited in our closest relatives. An important aspect of auditory-motor entrainment is that not all forms of rhythmic stimulation motivate movement to the same degree. This variation is captured by the concept of musical groove: high-groove music stimulates a strong desire for movement, whereas low-groove music does not. Here, we utilize this difference to investigate the neurophysiological basis o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
37
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 38 publications
(42 citation statements)
references
References 66 publications
5
37
0
Order By: Relevance
“…Intriguingly, when a similar paradigm was applied to humans, only females spent more time in locations when they heard consonant sounds. Sex differences in humans’ reaction to musical stimuli are rarely tested but have been described (Bowling et al 2019 ; Nater et al 2006 ; Wuttke-Linnemann). Still, that males did not spend more time with consonant stimuli was surprising, as the traditional survey-based tests of consonance preferences for humans have not produced any evidence of sex differences of which we are aware.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Intriguingly, when a similar paradigm was applied to humans, only females spent more time in locations when they heard consonant sounds. Sex differences in humans’ reaction to musical stimuli are rarely tested but have been described (Bowling et al 2019 ; Nater et al 2006 ; Wuttke-Linnemann). Still, that males did not spend more time with consonant stimuli was surprising, as the traditional survey-based tests of consonance preferences for humans have not produced any evidence of sex differences of which we are aware.…”
Section: Discussionmentioning
confidence: 99%
“…Sex differences in budgerigar acoustic preferences were shown in a previous place preference study (Hoeschele and Bowling 2016 ). For humans, sex differences in acoustic perception have sometimes been found (Bowling et al 2019 ; Nater et al 2006 ; Wuttke-Linnemann 2019 ), and while sex differences in human consonance perception have not been reported, it is not clear that they have been investigated. For these reasons and for parallelity, we analysed the data for each sex separately as well in both humans and budgerigars using the same tests as described above.…”
Section: Methodsmentioning
confidence: 99%
“…Previous studies with the pupillometry method have shown its ability to measure the moment-by-moment changes in cognitive and affective arousal during music listening (e.g., Laeng et al, 2016;Bowling et al, 2019). To our knowledge, there are no previous pupillometry studies during a musical performance.…”
Section: Pupillometry Of Playing Listening and Imagining Musicmentioning
confidence: 92%
“…Notably, even just music listening triggers high arousal (e.g., Gingras et al, 2015;Laeng et al, 2016;Weiss et al, 2016;Bowling et al, 2019). To our knowledge, no studies have applied eye pupillometry to the study of ''musical effort'' during the performance.…”
Section: Musical Effortmentioning
confidence: 99%
“…This effect might be attenuated, however, if participants are actively engaged in another task like having a conversation, as in the present case. An alternative possible explanation for the relation between groovy music and romantic interest is that groove-enhanced arousal levels might be misattributed to romantic interest (Marin et al, 2017;Bowling et al, 2018). Again, this possibility would need to be explored in future research.…”
Section: Discussionmentioning
confidence: 99%